Extracellular RNA: mechanisms of it’s transporting into target cells - Kuan-Chen Lu; Yujing Zhang; Eli Song (ExRNA)
Abstract Extracellular RNA (exRNA) is a type of RNA fragment that presents in extracellular fluids with highly stable features. It is carried by vesicles, such as exosomes, apoptotic bodies and other microvesicles, or associated with protein complexes or high-density lipoprotein (HDL). Literature in the past ten years has reported the species of exRNAs in biofluids and the carriers or mediators in exRNA involved cell-to-cell communication. Recently, studies have identified exRNAs to be biomarkers for cancer and other diseases. In addition, mechanisms of exRNA uptake in recipient cells have been reported, especially exosome-mediated transfer. In this review, we will focus on the relevance between exRNAs and their carriers. Furthermore, we will describe the possible ways target cells uptake these carriers with exRNAs.